2017
DOI: 10.1016/j.gdata.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative genome analysis of Cercospora sojina with other members of the pathogen genus Mycosphaerella on different plant hosts

Abstract: Fungi are the causal agents of many of the world's most serious plant diseases causing disastrous consequences for large-scale agricultural production. Pathogenicity genomic basis is complex in fungi as multicellular eukaryotic pathogens. Here, we report the genome sequence of C. sojina, and comparative genome analysis with plant pathogen members of the genus Mycosphaerella (Zymoseptoria. tritici (synonyms M. graminicola), M. pini, M. populorum and M. fijiensis - pathogens of wheat, pine, poplar and banana, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, the relative abundances of other microbial taxa that include some plant pathogens, such as Mycosphaerella , were enhanced in R soils (Figure 7G). Mycosphaerella species can cause leaf-spot disease in economically important crops including wheat, soybean, banana, citrus, and eucalyptus (Stukenbrock et al, 2011; Ohm et al, 2012; Zeng et al, 2017). In addition, the relative abundance of the bacterial order Xanthomonadales was increased in R soils (Figure 7C).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative abundances of other microbial taxa that include some plant pathogens, such as Mycosphaerella , were enhanced in R soils (Figure 7G). Mycosphaerella species can cause leaf-spot disease in economically important crops including wheat, soybean, banana, citrus, and eucalyptus (Stukenbrock et al, 2011; Ohm et al, 2012; Zeng et al, 2017). In addition, the relative abundance of the bacterial order Xanthomonadales was increased in R soils (Figure 7C).…”
Section: Discussionmentioning
confidence: 99%
“…Genome organizational changes have significant implications in coordinated gene expression ( 29 ), genome-specific specialization, ( 30 ) and the discovery of orthologous genes ( 31 ). CoGe’s provides powerful tools for exploring changes in genome structure and sequence evolution across multiple species, and making inferences on the evolutionary mechanisms and forces behind them.…”
Section: The Coge Web-based Platformmentioning
confidence: 99%
“…A broad comparative genomic study of three Trichoderma species has also been reported, which included comparison of their CAZyme genome content ( Schmoll et al. 2016 ), as well as a study in which genomes of five plant pathogenic species of the genus Mycosphaerella were compared ( Zeng et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%